Analisis Perbedaan Jumlah Bakteri Pada Ikan Nila (Oreochromis niloticus) Budidaya - Kamelia, Marlina; Widiani, Nurhaida; Adistyaningrum, Nurul (Biospecies, 2018)
Fish have good prospect to be developed because have high economic value. However, the percentage of bacterial fish diseases reached 33.9%. Tilapia (O. niloticus) is one of the most common bacteria. The TPC results of tilapia ponds of I, II, and III cultivation are 1.32 X 105 Cfu/g; 1.7 X 105 Cfu/g; 1.14 X 105 Cfu/g. From the results of physics measurement parameters of three ponds cultivation is still in accordance with the classification of water quality, but if viewed from the results of chemical measurement parameters pond culture II pertained water polluted.